Ampel Heritage Tourism Area in The Context of Sustainability - Galuh Fajarwati; Komang Ayu Laksmi Harshinta Sari; Faniah Shafira Amir Ishak (Center for Scientific Publication, 2020)
The city of Surabaya grows rapidly affecting the physical urban areas development, especially the tourist area. One of it is Ampel Region that is defined as a region of religious tourism and cultural heritage buildings by the city government as stated in Mayors Regulation Number: 188.45 / 251 / 402.1.104 / 1996. The area has potential for tourism and high economy development, but it does not compliment each other. So, it is necessary to review and analyse Ampel area to find a suggestion to harmonise the trade and economic development in order to continue supporting the function of the area as religious tourism. The methods used in this paper are descriptive approach and the application of sustainable development goals criteria, named four pillars of sustainability. Urban heritage plan will be developed specifically in the area of Ampel Mosque and street vendors (PKL) around it. The basic form of the tourist area has a broad scope, including the regional areas, specifically residential areas that will be affected by the system. However, this can improve the economy and income of the local communities. Reviewing and structuring this region will broaden up Ampel's impact to the life pattern of the people around. The results of this study are several physical elements such as infrastructure (circulation and parking), open space, socio-economic and sustainability improvement by providing solutions in the form of recommendations for the design of sustainability implementation and efforts to help non-physical problems in accordance with the results of the analysis of the Ampel area.